Sensitivitas Colletotrichum spp. pada Cabai terhadap Benomil, Klorotalonil, Mankozeb, dan Propineb - Desta Andriani; Suryo Wiyono; Widodo Widodo (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2017)
Anthracnose caused by several species of Colletotrichum is one of limiting factors for chilli production. Up to now the control of antrachnose disease still rely on regular and intensive application of synthetic fungicides. Application of similar active ingredients of synthetic fungicides may create resistance of the pathogens. This study was conducted to evaluate the sensitivity of three species of Colletotrichum against four commercial fungicides with different active ingredients, i.e. benomyl, chlorotalonil, mancozeb, and propineb. The sensitivity level and the potential occurrence of resistance of Colletotrichum were observed based on relative inhibition rate using poisoning food method. The results showed that all isolates were highly resistant to chlorotalonil, even up to ten times of the highest recommended concentrations. The tested fungal isolates were resistant or highly resistant to the recommended concentrations of mancozeb and propineb, but they were still sensitive when the concentrations were increased up to five times. Isolates of Colletotrichum spp. showed sensitive to highly sensitive response to benomyl.